Repeated bouts of load carriage alter indirect markers of exercise‐induced muscle damage, liver enzymes, and oxygen‐carrying capacity in male soldiers - Chad R. Straight; Kari L. McKenzie; Ava L. Sargent; Kenneth Racicot; Adrienne Hatch‐McChesney; Tshinanne V. Ndou; Kevin S. O'Fallon (Physiological Reports)
Abstract Soldiers are often required to carry heavy external loads over multiple days, which may degrade physical performance. We investigated the effects of repeated load carriage bouts on indirect markers of exercise‐induced muscle damage, liver enzymes, and oxygen‐carrying capacity in active‐duty infantrymen. Fourteen male soldiers (age = 24.6 ± 1.1 y; BMI = 25.7 ± 0.7 kg/m2) underwent a 5‐day protocol, consisting of baseline/familiarization, 3 load carriage bouts, and a recovery day. There were reductions in maximal voluntary contraction strength (p < 0.05), with the knee flexors and trunk extensors showing the greatest declines. Each load carriage bout produced an inflammatory response, including increases in leukocyte subtypes (neutrophils and monocytes) and monocyte chemoattractant protein‐1 (p < 0.05). At the end of the protocol, serum liver enzymes were elevated, and erythrocytes and hematocrit were lower than baseline (p < 0.05). In addition, greater circulating leukocytes at baseline predicted lower knee and trunk torque during recovery. Repeated bouts of load carriage reduce muscle strength and cause inflammation consistent with exercise‐induced muscle damage, alter liver function tests, and decrease oxygen‐carrying capacity in male soldiers, which could compromise readiness for prolonged and/or intense military operations.